2010
DOI: 10.1002/pro.425
|View full text |Cite
|
Sign up to set email alerts
|

Domain distribution and intrinsic disorder in hubs in the human protein–protein interaction network

Abstract: Intrinsic disorder and distributed surface charge have been previously identified as some of the characteristics that differentiate hubs (proteins with a large number of interactions) from non-hubs in protein-protein interaction networks. In this study, we investigated the differences in the quantity, diversity, and functional nature of Pfam domains, and their relationship with intrinsic disorder, in hubs and non-hubs. We found that proteins with a more diverse domain composition were over-represented in hubs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 36 publications
2
57
1
1
Order By: Relevance
“…Sequence diversity within this domain is observed in only two regions, one of which is the CH1-1 loop, suggesting that it may play a role in the functional diversity of Abs. In addition to its flexibility, the CH1-1 loop is also intrinsically disordered, at least in part, in more than one third of the structures in our dataset, which may suggest the existence of a functional binding site (60). Although the majority of Ab effector functions (e.g., complement activation and interaction with FcRs) are mediated by binding of the Fc, it was suggested that complement binding is also mediated by the CH1-1 loop.…”
Section: Discussionmentioning
confidence: 80%
“…Sequence diversity within this domain is observed in only two regions, one of which is the CH1-1 loop, suggesting that it may play a role in the functional diversity of Abs. In addition to its flexibility, the CH1-1 loop is also intrinsically disordered, at least in part, in more than one third of the structures in our dataset, which may suggest the existence of a functional binding site (60). Although the majority of Ab effector functions (e.g., complement activation and interaction with FcRs) are mediated by binding of the Fc, it was suggested that complement binding is also mediated by the CH1-1 loop.…”
Section: Discussionmentioning
confidence: 80%
“…As pointed out above, IDPs and IDRs can readily bind to multiple partners, so based on these observations, we proposed that the special features that enabled the evolution of complex networks containing hubs was IDPs and IDRs 25 . This proposal has been supported by a number of subsequent studies 47,[60][61][62][63][64][65] .…”
Section: Introductionmentioning
confidence: 72%
“…We further suggested two ways that disorder could be used by hub proteins for binding to multiple partners: (1) One region of disorder could bind to many different partners (one-to-many binding), so the hub protein itself uses disorder for multiple partner binding; and (2) many different regions of disorder could bind to a single partner (many-to-one binding), so the hub protein is structured but binds to many disordered partners via interaction with disorder. 8 Since this initial proposal, we [9][10][11] and many others [12][13][14][15][16][17][18][19][20][21][22] have provided additional evidence that hubs and/or their binding partners are especially enriched in intrinsic disorder, with both the many-to-one and one-to-many processes involving the use of intrinsic disorder.…”
Section: Introductionmentioning
confidence: 95%